MORPHOLOGICAL ANALYSIS OF STUDENTS’ AFFIX PATTERNS IN WRITING - Ika Lusi Kristanti (STKIP PGRI Jombang, 2016)
Affixation is a process that must be considered students in changing the form of words or word class. For example in changing an adjective into a noun, students must understand about the type of affixes used. For example, the word